In vivo performance of novel soybean/gelatin-based bioactive and injectable hydroxyapatite foams. (15th January 2015) - Kovtun, Anna; Goeckelmann, Melanie J.; Niclas, Antje A.; Montufar, Edgar B.; Ginebra, Maria-Pau; Planell, Josep A.; Santin, Matteo; Ignatius, Anita
Graphical abstract: Abstract: Major limitations of calcium phosphate cements (CPCs) are their relatively slow degradation rate and the lack of macropores allowing the ingrowth of bone tissue. The development of self-setting cement foams has been proposed as a suitable strategy to overcome these limitations. In previous work we developed a gelatine-based hydroxyapatite foam (G-foam), which exhibited good injectability and cohesion, interconnected porosity and good biocompatibility in vitro. In the present study we evaluated the in vivo performance of the G-foam. Furthermore, we investigated whether enrichment of the foam with soybean extract (SG-foam) increased its bioactivity. G-foam, SG-foam and non-foamed CPC were implanted in a critical-size bone defect in the distal femoral condyle of New Zealand white rabbits. Bone formation and degradation of the materials were investigated after 4, 12 and 20 weeks using histological and biomechanical methods. The foams maintained their macroporosity after injection and setting in vivo. Compared to non-foamed CPC, cellular degradation of the foams was considerably increased and accompanied by new bone formation. The additional functionalization with soybean extract in the SG-foam slightly reduced the degradation rate and positively influenced bone formation in the defect. Furthermore, both foams exhibited excellent biocompatibility, implying that these novel materials may be promising for clinical application in non-loaded bone defects.